HISTORICAL STUDY OF KOHAT DISTRICT: (1849-1947) - Shahid, Anum (Journal of Peace, Development and Communication, 2024)
Kohat is the capital of the Kohat District in Pakistan’s Khyber Pakhtun Khwa province. The current study investigated Kohat’s administrative history during the British period and measured the gradual change in the administrative profile and British-locals relationshop over time. The study’s primary focus variables were administrative changes. The study relied on documentary and official sources to collect factual data, while interviews were used to learn about social memory and people’s perceptions. The data was arranged thematically and was also cross-checked. Finally the study is written in narrative and descriptive style.